Pengolahan Limbah Organik Menggunakan Maggot Black Soldier Fly di Pokmas Landasan Ulin Tengah, Landasan Ulin - Hadi, Samsul; Rahmadina, Nazwa; Ramadani, Rizka Aulia; Nastiti, Kunti (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2024)
Waste management in Indonesia faces big challenges with thousands of tons of waste produced every day, including the condition of the Central Ulin Landscaping, the waste ends up in landfill without processing, causing environmental problems such as ground air pollution, methane emissions and the spread of disease. To overcome this, processing organic waste with Black Soldier Fly (BSF) maggots is an innovative and effective solution. BSF maggots can decompose organic waste quickly, produce quality compost and animal feed, while opeing up new economic opportunities for the community. The method used begins with preparation and planning, outreach and education, technical training, implementation and mentoring, market development and marketing, impact measurement and reporting. There was a reduction in the volume of organic waste by up to 60% within three months of implementing the program. The waste is processed into compost and animal feed. Produces around 200 kg of high quality compost per week which is used by local farmers and sold to local markets. The community produces around 50 kg of maggots per week as animal feed, thereby reducing dependence on commercial feed. People get additional income of IDR 500,000 to IDR 1,000,000 per month. This waste program increases public awareness about sustainable waste management through education and training, changing behavior in managing household waste. BSF Maggot is very effective in decomposing organic waste more quickly and efficiently than traditional composting methods. Changing people's behavior in separating organic waste from inorganic waste requires intensive education and outreach. In conclusion, the community service program carried out was able to overcome the problem of organic waste and provide significant economic and environmental benefits.